Repenser la ville : la construction des identités urbaines à travers la publicité touristique - Julie Manfredini (Confins)
Starting from 1889, time when the very first tourist office was created in Grenoble, many French cities followed and built a similar structure aiming to put forward and promote their urban spaces in order to favor tourism. Gathering the many trades interested in tourism business, these organisations would assemble many journalists. These autonomous associations, poor relation of tourism, are the origin of intense advert campaign that took various shapes. This well thought promotion is suggested by several actors, close collaborators of touristic offices like towns, tourism regional comity or local tourism associations, tend to give value to cities’ identity in order to face competition and distinguish themselves from nearby destinations. Local landscapes and estate known as inherent to the land identity are composing the core elements of this advert. Images conveyed from these advertising tools settle to stay and are progressively accepted by inhabitants. That is why through the study of this advert and its tools, it is on the one hand a matter of understanding its actors regarding the touristic profile of their cities, their amount of motivation and commitment to set up tourism in their territory especially for the enhancement of a cultural tourism, from the end of the XIXe century to today. On the other hand it is a matter of analysing the conception and evolution of urban tourism since the end of the XIXe century through the evolution of this touristic advert. Finally we would like to demonstrate the need of modernity in order to adapt to the fast evolution of tourism in order to perceive consequences on the representation of urban space.